Coaches' perceived benefits of school-sponsored adapted sport for students with disabilities - Baldwin, Cadi (My University, 2017)
Although laws require equal opportunities for all students, few students with disabilities (SWD) participate in school-sponsored extracurricular sport compared to nondisabled peers. Recently, more school-sponsored adapted sport (AS) programs have started around the country. Due to recent development there is minimal research on AS and the effects on SWD. This study examined coaches' perceived benefits of participation in AS. Questions included demographics, rating and ranking of benefits, and questions on coaching efficacy. Paired sample t-tests found a significant difference in social skills compared to other benefit categories. Personal skills and PA/fitness had significant differences compared to sport-specific skills, but not significantly different from each other. Triangulation of an opened ended question found similar results. Social skills were perceived more important than all other benefit categories. A one-way ANOV A found no significant difference in the rating of benefits based on coaches' gender. Multiple regressions found that motivation coaching efficacy had a significant impact on social skills, PA/fitness, and sport-specific skills. Game strategy coaching efficacy had a significant effect on sport-specific and personal skills. Multiple regressions found that as coaches gained more experience they valued social skill and PA/fitness more. Coaching experience did not affect coaches' ratings of sport-specific or personal skills.
Keywords: Sports activities; Kinesiology; Children with disabilities